2007
DOI: 10.1088/0964-1726/16/2/022
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional layer-by-layer carbon nanotube–polyelectrolyte thin films for strain and corrosion sensing

Abstract: Since the discovery of carbon nanotubes, researchers have been fascinated by their mechanical and electrical properties, as well as their versatility for a wide array of applications. In this study, a carbon nanotube-polyelectrolyte composite multilayer thin film fabricated by a layer-by-layer (LbL) method is proposed to develop a multifunctional material for measuring strain and corrosion processes. LbL fabrication of carbon nanotube composites yields mechanically strong thin films in which multiple sensing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
257
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(276 citation statements)
references
References 35 publications
(67 reference statements)
10
257
1
Order By: Relevance
“…The LbL process continues by immersing the substrate (and the initial monolayer) in a negatively charged 1.0 mg mL -1 MWNT (Cheap Tubes, less than 8 nm outer diameter) dispersed in 1.0 wt% poly(sodium 4-styrene sulfonate) (PSS, M w & 1 M, Sigma-Aldrich) solution. Similar to previous studies by Loh et al [33,34], MWNTs are dispersed via steric stabilization by subjecting the MWNT-PSS solutions to 180 min of bath sonication (135 W, 42 kHz) followed by 30 min of high-energy tip sonication (3.178 mm tip, 150 W, 20 kHz). It should be noted that MWNTs are used due to their intrinsic metallic nature and high electronic conductivities, whereas SWNTs can possess metallic or semi-conducting properties.…”
Section: Lbl Thin Film Assemblymentioning
confidence: 84%
See 2 more Smart Citations
“…The LbL process continues by immersing the substrate (and the initial monolayer) in a negatively charged 1.0 mg mL -1 MWNT (Cheap Tubes, less than 8 nm outer diameter) dispersed in 1.0 wt% poly(sodium 4-styrene sulfonate) (PSS, M w & 1 M, Sigma-Aldrich) solution. Similar to previous studies by Loh et al [33,34], MWNTs are dispersed via steric stabilization by subjecting the MWNT-PSS solutions to 180 min of bath sonication (135 W, 42 kHz) followed by 30 min of high-energy tip sonication (3.178 mm tip, 150 W, 20 kHz). It should be noted that MWNTs are used due to their intrinsic metallic nature and high electronic conductivities, whereas SWNTs can possess metallic or semi-conducting properties.…”
Section: Lbl Thin Film Assemblymentioning
confidence: 84%
“…Previous studies conducted by Loh et al [33,34] have shown that homogeneous carbon nanotube-PE thin films with no phase segregation can be fabricated by depositing nanometer-thick monolayers of alternating charged PE and nanomaterials (Fig. 1).…”
Section: Lbl Thin Film Assemblymentioning
confidence: 98%
See 1 more Smart Citation
“…Polyanions and polycations have been used to prepare self-assembled nano-and microstructures for various applications (Kotz et al, 2001;Ariga et al, 2008). Self-assembly controlled through layer-by-layer (LbL) strategy has shown potential in preparation of delivery systems to smart sensors (Loh et al, 2007;Johnston et al, 2006;Yang et al, 2006;Hammond, 2011). Since the initial reports from Decher and colleagues, there has been a tremendous increase in the number of publications reporting varied applications of self-assembly through LbL strategy (Decher et al, 1992;Decher, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several different groups have deposited modified carbon nanotubes on various substrates for different applications by the ionic LbL approach. [11][12][13][14] In the present work, we have used LbL assembly on separately deposited conducting, transparent SWCNT electrodes rather than incorporate SWCNTs into LbL films. Carrillo et al 15 have used the LbL technique to coat the SWCNT surface with gold nanoparticles and polyelectrolytes, but their approach is more tedious and requires several steps of cross-linking.…”
Section: Introductionmentioning
confidence: 99%